2011
DOI: 10.3390/molecules16064482
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Composition of Hydrochlorothiazide:β-Cyclo-dextrin: Preparation by Three Different Methods, Physico-Chemical Characterization and In Vivo Diuretic Activity Evaluation

Abstract: Hydrochlorothiazide is a common diuretic antihypertensive drug of the thiazide family. Its poor aqueous solubility is one of the reasons for its limited bioavailability after oral administration. This work aimed at the development of a hydrochlorothiazide:β-cyclodextrin (HTZ:β-CD) pharmaceutical composition in order to improve water solubility and bioavailability of the drug. The HTZ:β-CD complexes were prepared by three different methods: spray-drying, freeze-drying and fluid bed. Complexes were characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 33 publications
1
15
0
Order By: Relevance
“…Some of these studies also found that the physicochemical properties depended on the method used for complex formation [20]. In further experiments, it would be interesting to investigate whether different complex morphologies lead to different bioavailabilities in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…Some of these studies also found that the physicochemical properties depended on the method used for complex formation [20]. In further experiments, it would be interesting to investigate whether different complex morphologies lead to different bioavailabilities in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…CDs are widely used to enhance the aqueous solubility of drugs [1214] since the physicochemical properties of the guests (solubility, stability, bioavailability, antimicrobial activity, etc .) are altered upon complexation.…”
Section: Introductionmentioning
confidence: 99%
“…The ternary inclusion complex containing HPMC kneaded complex showed 97.99% drug release within 10 minutes. The enhancement of dissolution was due to formation of inclusion in solid state with reduction in crystallinity of HCT as confirmed by FTIR studies, leading to increased hydrophilicity higher effect and increase contact between drug and carrier [5,6,12].…”
Section: Dissolution Studiesmentioning
confidence: 99%
“…Host:guest interaction of HCT, βCD, and HPMC observed in spectra. It showed disappearance of OH deformation band of water molecule of CD cavity [5,6].…”
Section: Ftir Spectroscopymentioning
confidence: 99%